The Influence of Wearable Device Technology on Enhancing Student Learning Outcomes: A Comprehensive Study - Nafil Khairil Hanif; Ekha Nova (Journal of Education Innovation and Curriculum Development, 2024)
The rapid advancement of wearable device technology has introduced new opportunities to enhance educational practices and student learning outcomes. This research investigates the impact of wearable device usage on improving students' academic performance, engagement, and self-regulation. Through a mixed-method approach involving surveys and observational studies, the findings reveal that wearable devices positively influence learning by promoting time management, providing real-time feedback, and encouraging active participation. However, challenges such as accessibility, potential distractions, and data privacy concerns also emerged. Comparisons with previous research confirm the consistent benefits of wearable technologies while highlighting the need for careful implementation and policy development. The study concludes that with strategic integration, wearable devices can serve as valuable tools to foster improved learning experiences, suggesting further longitudinal research and inclusive practices to maximize their potential in diverse educational settings.